Gen Z Legal Talent, How Indonesian Law Firm Can Effectively Retain This Generation in The Firm - Lubis, Debu Batara (Riviera Publishing, 2025)
The research examines the perceived and real engagement of Gen Z lawyers at a small boutique law firm in Jakarta. To assess both perceived and real engagement of the Gen Z lawyers at a small boutique law firm in Jakarta, the writer is conducting a research by using a mixed-methods approach of structured questionnaires and in-depth interviews to measure the seven dimensions of engagement framework – Pride to the Company, Positive Criticism, Proactive Attitude, Energy, Resilience, Action to Promote the Company, and Intention to Stay. The research exposed that although the questionnaire shows a moderate to high level engagement, the interview presents facts that are indicating lower behavioral engagement in most key indicators. The discrepancies (as measured through the gap score) suggest that the Gen Z lawyers may in theory express their engagement but still facing a real challenge in practicing the same, as may be triggered by lack of psychological safety, superficial emotional connection, low initiative taking behavior, and fatigue. However, the research also uncovers positive facts of hidden strength in both resilience and intention to stay, which suggest the Gen Z lawyers potential for long-term commitment to the firm, if it is nurtured correctly. To enhance the retention, law firm must bridge the engagement gaps and accommodate Gen Z generational needs of psychological safety, purposeful work, empowerment, career development, wellbeing, and social connections.